The Impact of Correction Center Formal Education Program on Offenders’ Psychosocial Development the Case of Delo Mena, Goba and Sheshamene Correction Centers Primary Schools Bale-West Arsi Oromia South East Ethiopia - Badasa, Gamachu Gishe (2020)
The main objective of this study was to identify the impact of formal Correction education program on offenders’ psychosocial development. For an in-depth investigation of Correction Center education, case study design was employed. The sampling technique used to select research participants was mainly purposive for the reason that it enables us to get individuals directly engaged in the practices of correction Centers primary schools. Thus, prisoners who are attending formal school, the respective head of selected Correction Centers, counselors, education coordinators, school principals, their teachers and education office heads were selected. Semi-structured interview guides were held with different participants to explore in-depth, rich, and seek to understand results of data that are unexpected. Besides, the researchers were selected three focus group meaning independently one group of experienced teachers and students at the respective Correction schools where one of the section criteria is homogeneity of people among many other inclusion rules. Data was transcribed and translated into English language for analysis. Correspondingly, findings relevant to the objective of the study was selected, Coded, organized, analyzed, presented, and discussed thematically in line with the objectives set. The study suggested that if facilities and an opportunity will be given for all who need it there is no doubt that correction center education would have positive impact on learners’ psychosocial makeup. For instance, the school principal at Goba Correction was explained it as for the one who attend it seriously he/she can be effective. There are people who got a chance of education at their adulthood. Key informants assumed that these people do not have such opportunity if they were at home because the masses are youth and adult whose appropriate education modality via non-formal. So in this regard, Correction Center education is reducing illiteracy since the mainstream educational level is illiterate. More importantly, teachers at Goba Correction School were replied, as there were individuals who have continued learning until university and graduated from it and became employed in different organizations. It was found that those detainees on education program have been the first beneficiaries of parole and excuse given by government every New Year Keywords: Bale-West Arsi, Impact, Correction Education, General Education, Rehabilitation DOI: 10.7176/PPAR/10-6-01 Publication date:June 30th 202